The European Higher Education Area in 2015: Bologna Process Implementation Report - Eurydice (Commission européenne, 2015)
The 2015 report has been prepared for the European Ministerial Conference in Yerevan, Armenia on 14-15 May 2015. It provides a snapshot of the state of implementation of the Bologna Process from various perspectives using data collected in the first half of 2014. It provides both qualitative information and statistical data, and covers all main aspects of higher education reforms aiming at a well-functioning European Higher Education Area.